Nano-scavengers for blood biomarker discovery in ovarian carcinoma. (October 2020) - Hadjidemetriou, Marilena; Papafilippou, Lana; Unwin, Richard D.; Rogan, Jane; Clamp, Andrew; Kostarelos, Kostas
Graphical abstract: Highlights: Clinical exploitation of protein corona fingerprinting as a novel tool for blood proteomics analysis and biomarker discovery. Proteomic analysis of the liposomal corona to amplify and uncover disease specific signatures in the blood of ovarian cancer patients. Discovery of previously unknown potential biomarker proteins in ovarian carcinoma with higher specificity and sensitivity than the clinically used biomarkers. Abstract: The development and implementation of biomarker-based screening tools for ovarian cancer require novel analytical platforms to enable the discovery of biomarker panels that will overcome the limitations associated with the clinically used CA-125.The systematic discovery of protein biomarkers directly from human plasma using proteomics remains extremely challenging, due to the wide concentration range of plasma proteins. Here, we describe the use of lipid-based nanoparticles (NPs) as an 'omics' enrichment tool to amplify cancer signals in the blood and to uncover disease specific signatures. We aimed to exploit the spontaneous interaction of clinically-used liposomes (Caelyx®) with plasma proteins, also known as' protein corona' formation, in order to facilitate the discovery of previously unreported differentially abundant molecules. Caelyx® liposomes were incubated with plasma samples obtained from advanced ovarian carcinoma patients and healthy donors and corona-coated liposomes were subsequently recovered. Comprehensive comparison between 'healthy' and 'diseased' corona samples by label-free proteomics resulted in the identification of multiple differentially abundant proteins. Moreover, immunoassay-based validation of selected proteins demonstrated the potential of nanoparticle-platform proposed to discover novel molecules with great diagnostic potential. This study proposes a nanoparticle-enabled workflow for plasma proteomic analysis in healthy and diseased states and paves the way for further work needed to discover and validate panels of novel biomarkers for disease diagnosis and monitoring.